STRATEGIES FOR DEVELOPING THE CONCEPT OF EDUCATIONAL RESOURCE MANAGEMENT IN IMPROVING SCHOOL QUALITY - Muhammad Ali Hasyimi Muhammad Ali Hasyimi; Zubaidah , Zubaidah (STAI Nusantara Kota Banda Aceh, 2024)
Educational resource management in Indonesia faces challenges such as the unequal distribution of teachers, limited infrastructure, and low utilisation of technology. Additionally, inefficient fund management and lack of community involvement hinder the improvement of educational quality. This study aims to analyse the importance of integrated educational resource management in improving school quality. The methodology used is library research, collecting data from relevant literature and reports. The findings indicate that data-driven strategies, cross-sector collaboration, and an organisational culture that supports collaboration can improve efficiency. Integrated management optimises resources and sustainably improves education quality.